Flower-like hierarchical ZnS-Ga2S3 heterojunction for the adsorption-photo-reduction of Cr(VI). (December 2020) - Qi, Yongchao; Fan, Yingjun; Liu, Tingting; Zheng, Xiaogang
Abstract: Adsorption-photo-reduction is considered as a potential route to remove Cr(VI) from wastewater. To explore the novel photocatalysts with efficient adsorption-photocatalytic activity, flower-like hierarchical ZnS-Ga2 S3 heterojunction was prepared for the solar-light-driven reduction of Cr(VI). Its adsorption-photocatalytic capacity is greatly affected by the ZnS/Ga2 S3 molar ratio, Cr(VI) content, pH values, and inorganic ions. Among these obtained composites, ZnS-Ga2 S3 -3 with a ZnS/Ga2 S3 molar ratio of 3:1 exhibits the best adsorption-photocatalytic capacity. The adsorption capacity of ZnS-Ga2 S3 -3 is 54.42 mg g −1, and its total removal efficiency is 99.10% for 100 mg L −1 Cr(VI) solution after 160 min. In addition, the adsorption-photo-reduction performance of ZnS-Ga2 S3 -3 is slightly deactivated after nine cycle times. The Langmuir, pseudo-second-order, and first-order models well describe the adsorption isotherm, adsorption kinetic, and photo-reduction kinetic of ZnS-Ga2 S3 -3, respectively. The synergy effect of ZnS and Ga2 S3 are favorable for the efficient transfer and separation of charge carriers, and provide sufficient vacant sites at the junction interface for the adsorption of Cr(VI). Graphical abstract: Image 1 Highlights: Flower-like hierarchical ZnS-Ga2 S3 was prepared by the hydrothermal route. ZnS-Ga2 S3 heterojunction has excellent adsorption-photocatalysis capacity. ZnS-Ga2 S3 exhibits slight deactivation for Cr(VI) removal after nine cycle times.